A pre-column derivatization method allowing quantitative metabolite profiling of carboxyl and phenolic hydroxyl group containing pharmaceuticals in human plasma via liquid chromatography-inductively coupled plasma-tandem mass spectrometry (LC-ICP-MS/MS). Issue 2 (29th January 2018) - Li, Sanwang; Klencsár, Balázs; Balcaen, Lieve; Cuyckens, Filip; Lynen, Frederic; Vanhaecke, Frank
Abstract : Novel analytical strategies for investigating drug ADME (absorption, distribution, metabolism and excretion). Abstract : The development of suitable analytical methods for drug ADME (absorption, distribution, metabolism and excretion) studies is of great importance. The currently routinely applied detection techniques usually demonstrate a structure-dependent analytical response (MS-based method) or require the synthesis of a radiolabelled version of the parent drug (radiodetection) for accurate quantification. Inductively coupled plasma-(tandem) mass spectrometry (ICP-MS(/MS)) offers a promising alternative to radiolabelling followed by radiodetection due to the structure-independent nature of its analytical response. Within the context of this study, an accurate, simple and sensitive HPLC-ICP-MS/MS method for the quantitative metabolite profiling of diclofenac in human plasma based on the pre-column derivatization of the carboxylic and phenolic –OH groups present in the parent drug and its major metabolite, 4′-hydroxy-diclofenac, was developed and validated. A cost-effective and commercially available derivatization reagent, p -bromophenacyl bromide ( p -BPB), was applied for the introduction of Br into the drug molecule and its major metabolite, enabling the element-selective detection and quantification based on the Br-signal. The presence of Cl in both diclofenac and 4′-hydroxy-diclofenac allowed an additional validation via simultaneous monitoring of the Cl-signal by using a state-of-art ICP-MS/MS instrument equipped with a collision/reaction cell. The reaction conditions were successfully optimized to achieve a quantitative formation of the corresponding derivatization products, while the baseline separation of the target compounds in a typical biological matrix ( i.e. human plasma) was achieved using gradient reversed phase high-performance liquid chromatography (RP-HPLC). A fit-for-purpose accuracy (recovery between 85–115%) and precision (repeatability ≤7.2% RSD) were achieved. The limits of quantification (LOQ) are ≈50 μg L −1 for Br and ≈80 μg L −1 for Cl, corresponding to ≈0.2 mg L −1 and ≈0.4 mg L −1 of diclofenac, respectively.